EVALUASI PENCAPAIAN MILLENIUM DEVELOPMENT GOALS BIDANG KESEHATAN DI KABUPATEN PATI TAHUN 2011 ( Achievement Evaluation Of Health Programs Millennium Development Goals In Pati Regency 2011) - Dewi Cahyaningrum (Journal of Politic and Government Studies, 2013)
Abstract:Health is an important part of human life. Because if people are not healthy, will not beable to move and greatly affect their performance. Unhealthy conditions can be causedby various diseases spread by viruses or bacteria. According to WHO data, there aremore than 10 kinds of harmful and deadly diseasesin the world. Some of them are quitedangerous because the disease can be fatal for the sufferer, such as HIV / AIDS,malaria, dengue, and tuberculosis. The declining health of the world, raising awarenessfrom United Nations to achieve millennium development goals. Most of them arecommitted to improving the health of people in the world that improve maternal andchild health, and reduce the spread of infectious diseases.Key words: Health, Various Diseases, Millenium Development Goals.